KUALITAS PELAYANAN TRANSPORTASI DAMRI DI SULAWESI UTARA - Purukan, Johanes; Posumah, Johnny; Pombengi, Jericho Denga (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT : This study aims to describe the quality of service of transport, especially transport Damri pioneers in North Sulawesi in the development of the science of public administration. The Ministry is exercised by the public company Damri based on Government Regulation No. 31 of 2002 on the establishment of the public company damri, was founded to help problems in terms of transportation. However, in practice as well as the fact that there is a phenomenon of issues management and service, like many vehicles that are not worthy of wearing, not precise time in his Ministry, operational system procedures are unclear and the fare price. The research methods used in this research is a descriptive study of qualitative methods, with the techniques of primary and secondary data collection is done with the interview, observation and documentation study. As for the informant, among others: 1head of the station, 2 drivers, 2 conductor, and 7 people pioneering service user community. In the discussion of the quality of service of transport damri in North Sulawesi is related to aspects of the Tangibles, Reliability, Responsiveness, assurance and empathy can be said to have not been fullest. It is proven by the provision of the facilities, such as a waiting room, and the toilet is not yet available. In addition the complaint room service complaints also have not provided by damri public company said. Based on the discussion and conclusions on the above then suggest Damri Public Company manado station must provide to the passenger waiting room, and make a toilet in each existing fleet. In addition the need for improvements on the seat because it was not appropriate. The Damri Public Company will also have to provide media services complaints such as hot-line service. Keywords: Quality of service transportation, Damri